Flipping a Phosphate Switch on Kinesin-II to Turn IFT Around - Craige, Branch (Dev Cell, 2014)
Cilia and flagella are assembled and maintained by the motor-driven, bidirectional traffic of large protein complexes in a process termed intraflagellar transport (IFT). In this issue of Developmental Cell, Liang et al. (2014) report that IFT is regulated in part by the phosphorylation status of the kinesin-II subunit FLA8/KIF3B.